Maximizing Nano-Silica Efficiency in Laboratory-Simulated Recycled Concrete Aggregate via Prior Accelerated Carbonation: An Effective Strategy to Up-Cycle Construction Wastes - Cheng-Gong Lu; Xiu-Cheng Zhang; Xue-Fei Chen (Molecules)
Herein, the study explores a composite modification approach to enhance the use of recycled concrete aggregate (RCA) in sustainable construction by combining accelerated carbonation (AC) and nano-silica immersion (NS). RCA, a major source of construction waste, faces challenges in achieving comparable properties to virgin aggregates. Nano-silica, a potent pozzolan, is added to fill micro-cracks and voids in RCA, improving its bonding and strength. AC pretreatment accelerates RCA’s natural carbonation, forming calcium carbonate that strengthens the aggregate and reduces porosity. Due to the complexity of the original RCA, a laboratory-simulated RCA (LS-RCA) is used in this study for the mechanism analysis. Experimental trials employing the composite methodology have exhibited noteworthy enhancements, with the crushing index diminishing by approximately 23% and water absorption rates decreasing by up to 30%. Notably, the modification efficacy is more pronounced when applied to RCA derived from common-strength concrete (w/c of 0.5) as compared to high-strength concrete (w/c of 0.35). This disparity stems from the inherently looser structural framework and greater abundance of detrimental crystal structures in the former, which impede strength. Through a synergistic interaction, the calcium carbonate content undergoes a substantial increase, nearly doubling, while the proportion of calcium hydrate undergoes a concurrent reduction of approximately 30%. Furthermore, the combined modification effect leads to a 15% reduction in total porosity and a constriction of the average pore diameter by roughly 20%, ultimately resulting in pore refinement that equates the performance of samples with a water-to-cement ratio of 0.5 to those with a ratio of 0.35. This remarkable transformation underscores the profound modification potential of the combination approach. This study underscores the efficacy of harnessing accelerated carbonation in conjunction with nano-silica as a strategic approach to optimizing the utilization of RCA in concrete mixes, thereby bolstering their performance metrics and enhancing sustainability.